PUBLIC SERVICE COMMUNICATION IN THE INDONESIAN BORDER AREAS - Zen Amiruddin; Muslimin Machmud; Salahudin Salahudin (University of Muhammadiyah Malang, 2023)
This study aimed at examining the patterns and strategies of public service communication in Indonesian border areas, especially those carried out by the BNPP-RI as the management agency of the state border areas. The study focuses on the public service communication of BNPP-RI in their Twitter social media account @bnpp_ri. This study employed a descriptive-qualitative approach by utilizing the Nvivo12 analysis tools as the data processing tool. Several aspects investigated to find out the communication patterns of BNPP's public services on Twitter were communication types, communication intensity, actor relations, dominant topics, and other related aspects. The study results found that BNPP, in its Twitter account, has been quite capable of utilizing digital platforms as an alternative to public service communication in the Indonesian border areas. On the other hand, some shortcomings were also indicated. For example, When viewed from content intensity, Twitter account @bnpp_ri was deemed volatile. Furthermore, @bnpp_ri is also considered unable to dominantly involve other actors/accounts in establishing the public service communication on Twitter. BNPP must address these shortcomings to optimize the communication pattern of public services on Twitter. It is also vital to consider the fundamental role of BNPP as an active agency in communicating its public services in the border areas of the Republic of Indonesia.